Low Rate of Perinatal Sepsis in Term Infants of Mothers with Chorioamnionitis - Braun, David; Bromberger, Patricia; Ho, Ngoc J.; Getahun, Darios (American Journal of Perinatology, 2016)
Objective The risk of infection in infants of mothers with chorioamnionitis (CAM) may be lower than previously reported. This study's objective was to determine the incidence of intrapartum fever (IPF) and culture-positive early-onset bacterial neonatal infection (CPEOI) in the late preterm and term infants of mothers with or without CAM and to assess interhospital variation in neonatal infection management.Study Design This retrospective cohort study included mothers and newborns delivered at ≥35 weeks gestation at Kaiser Permanente Southern California Hospitals in 2010 (n = 31,112). Electronic medical and laboratory records from 13 medical centers were examined for maternal temperature, intrapartum, and neonatal antibiotic treatment. Rates for IPF, CAM, and CPEOI were estimated. Rates for starting neonatal antibiotics were calculated.Results The incidence of IPF was 9% and CAM 4%. The overall rate for CPEOI was 0.61/1,000 (95% confidence interval [CI] 0.34, 0.89/1,000). The rate of CPEOI was 4.0/1,000 (95% CI 0.50, 7.5/1,000) in infants born to mothers with CAM. The rate of beginning antibiotics for infants born to mothers with CAM ranged from 7 to 76% between nurseries.Conclusion The rate of CPEOI in infants born to mothers with CAM is lower than previously reported. There is heterogeneity in initiation of neonatal antibiotics by neonatologists.
Keywords: chorioamnionitis; neonatal infection; antibiotic use; antibiotic prophylaxis; group B streptococcus